Effects of operating factors for an axial-flow corn shelling unit on losses and power consumption - Srison, Waree; Chuan-Udom, Somchai; Saengprachatanarak, Khwantri (Agriculture and Natural Resources, 2016)
The operating factors were studied for an axial-flow corn shelling unit that affected losses and power consumption. The shelling unit was 0.90 m long, with a diameter toward the end of the peg tooth of 0.30 m. The factors comprised three levels of moisture content (MC), three levels of feed rate (FR), and three levels of rotor speed (RS). The experiments were conducted based on response surface methodology and 23 factorial designs. The results of this study indicated that the MC significantly affected grain breakage and power consumption, but did not affect shelling unit losses. Increasing the MC increased both the grain breakage and power consumption. The FR affected the power consumption but did not affect shelling unit losses and grain breakage. Increasing the FR increased the power consumption. The RS had a significant impact on the shelling unit losses, grain breakage and power consumption. Increasing the RS increased the grain breakage and power consumption, but decreased the shelling unit losses. Empirical models were formulated based on multiple linear models.